THE MEANINGS OF LEARNING AND TEACHING MATHEMATICS IN THE VOICES OF STUDENTS FOR TEACHERS - Muñoz López, Camila Ximena (2024)
This article is derived from the research titled A narrative look at the meaning of the experience of being a primary school teacher who teaches mathematics. The results presented here obey the objective of recognizing the meanings that some students of the Bachelor's Degree in Primary Basic Education of the National Pedagogical University (Colombia) give to their learning and teaching experiences of mathematics. This research adopted a qualitative approach, using the case study method. To collect data, narrative interviews were designed. Four participants were selected, all of them student teachers from the 2019-2 cohort of the bachelor's degree. We identified some fears and difficulties towards/with mathematics, which have been positively transformed into empowerment. We recognized the meanings given to the experience of learning and teaching mathematics, based on reflective practice, which becomes a commitment as future teachers.